2018
DOI: 10.1080/00071668.2018.1483577
|View full text |Cite
|
Sign up to set email alerts
|

Effect of herbal feed additives on performance parameters, intestinal microbiota, intestinal morphology and meat lipid oxidation of broiler chickens

Abstract: 1. This feeding trial investigated the effects of herbal feed additives on performance of broiler chickens, jejunal and caecal microbiota, jejunal morphology, meat chemical composition and oxidative stability during refrigerated storage. 2. In a 42 days trial, 320 one-day-old broiler chickens were randomly allocated to 4 groups with 4 replicate pens each containing 20 chicks. The control group was fed maize-soybean-based diets. The diets of the other three groups were supplemented with herbal feed additives: H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 54 publications
7
39
1
Order By: Relevance
“…We found that a dysbiosis was present in the infected control, whereas increased numbers of lactic acid bacteria were identified in the groups receiving the dietary polyherbal formula. These results are in agreement with our previous studies, where similar herbal mixtures increased lactic acid bacteria [12,50].…”
Section: Discussionsupporting
confidence: 94%
“…We found that a dysbiosis was present in the infected control, whereas increased numbers of lactic acid bacteria were identified in the groups receiving the dietary polyherbal formula. These results are in agreement with our previous studies, where similar herbal mixtures increased lactic acid bacteria [12,50].…”
Section: Discussionsupporting
confidence: 94%
“…Clearly, it is observed that the dietary supplementation with CLP improved the growth of the cecal LABs and gut health in broilers, which is related to the higher percentage of viability with T1, as well as some changes in the carcass traits in the treatments where this natural product was used (Table 3, 4 and 5). According to Rafeeq et al (2016) and Giannenas et al (2018) the use of phytobiotic additives (from Cuminum cyminum L., Foeniculum vulgare Mill. and Achillea wilhemsii C. Koch; Magnifera indica L., Withania somnifera L., Phyllanthus emblica L. and Ocimum sanctum L., respectively), increased the cecal lactic acid bacteria (LABs) count, which improved intestinal permeability and nutrient digestibility.…”
Section: Resultsmentioning
confidence: 99%
“…However, the use of anticoccidial substances and ionophores is still permitted in broiler feeds within the EU. It must be noted that a different legislation frame exists in Canada, the USA, and some other parts of the world regarding drug-free broiler chicken production, where use of anticoccidial as well as antibacterial drugs is restricted (1,2). This situation represents a great challenge to the poultry industry; coccidiosis persists as a problem and remains a major predisposing factor for the occurrence of necrotic enteritis and other pathogenic diseases (3,4).…”
Section: Introductionmentioning
confidence: 99%